Dictionnaire Dan - Français (dan de l'Est) - Vydrine, Valentin; Vydrine, Valentin (MeaBooks Inc, 2015)
Eastern Dan-French dictionary, preceded by a grammar sketch, is the first and only dictionary of this language spoken in Western C?te d'Ivoire by half a million people. Both in dictionary and in the grammar sketch, lexical and grammatical tones are marked throughout. Polysemy and idiomatics are broadly represented, dictionary entries include abundant illustrative examples reflecting the cultural specifics of Dan. The dictionary has a French-Dan index. The publication is oriented both to Dan languages learners and professional linguists; it can be also used by the native speakers of Dan.